HUBUNGAN KEHAMILAN GEMELI, ANEMIA, DAN HIPERTENSI TERHADAP TERJADINYA KEHAMILAN RESIKO TINGGI DI PUSKESMAS KUTARAYA KECAMATAN KAYUAGUNG KABUPATEN OKI - Yusendang, Sri (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2019)
High risk pregnancy is a condition that can affect the optimization of both the mother and the fetus in the pregnancy at hand. The research objective in this study was to determine the relationship between happy pregnancy, anemia, and hypertension to high-risk pregnancies at the Kutaraya Public Health Center, Kayuagung District, OKI Regency in 2019. The design of this study was quantitative using the Analytical Survey method using Cross Sectional. The research will be conducted in May-August 2020. The population in this study amounted to 905 pregnant women, with a sample of 89 respondents, taken by random sampling. From the analysis, it was found that there was no significant relationship between happy pregnancy and high-risk pregnancy with Pvalue + 0.526, there was a significant relationship between anemia (Pvalue = 0.009), and hypertension (Pvalue = 0.013) with high-risk pregnancy As for the suggestions for health workers, the results of this study are expected to provide information and input for evaluating midwifery work programs, especially pregnant women with high risk.